Morphological and molecular description of Sarcocystis ratti n. sp. from the black rat (Rattus rattus) in Latvia - Prakas, Petras; Kirillova, Viktorija; Gavarāne, Inese; Grāvele, Evita; Butkauskas, Dalius; Rudaitytė-Lukošienė, Eglė; Kirjušina, Muza (Parasitology research (1987), 2019)
Rodents have been widely studied as intermediate hosts of Sarcocystis ; however, only a few reports on these parasites in the black rat ( Rattus rattus ) are known. Having examined 13 black rats captured in Latvia, sarcocysts were found in skeletal muscles of two mammals and were described as Sarcocystis ratti n. sp. Under a light microscope, sarcocysts were ribbon-shaped, 0.9–1.3 × 0.09–0.14 mm in size and had a thin (0.8–1.3 μm) and smooth cyst wall. The lancet-shaped bradyzoites were 8.3 × 4.3 (7.5–9.3 × 3.9–4.8) μm. Under a transmission electron microscope, the cyst wall was up to 1.3 μm thick, wavy, the ground substance appeared smooth, type 1a-like. Morphologically, sarcocysts of S . ratti were somewhat similar to those of S . cymruensis , S . rodentifelis , and S . dispersa -like previously identified in the brown rat ( Rattus norvegicus ). On the basis of 18S rDNA, 28S rDNA, and cox1 , significant genetic differences (at least 2.3, 4.5, and 5.8%, respectively) were observed when comparing S . ratti with other Sarcocystis species using rodents as intermediate hosts. While ITS1 sequences of S . ratti were highly distinct from other Sarcocystis species available in GenBank. Phylogenetic and ecological data suggest that predatory mammals living near households are definitive hosts of S . ratti .